2015
DOI: 10.1002/jlcr.3281
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of a high specific activity methyl sulfone tritium isotopologue of fevipiprant (NVP‐QAW039)

Abstract: The synthesis of a triple tritiated isotopologue of the CRTh2 antagonist NVP-QAW039 (fevipiprant) with a specific activity >3 TBq/mmol is described. Key to the high specific activity is the methylation of a bench-stable dimeric disulfide precursor that is in situ reduced to the corresponding thiol monomer and methylated with [(3)H3]MeONos having per se a high specific activity. The high specific activity of the tritiated active pharmaceutical ingredient obtained by a build-up approach is discussed in the light… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…This study revealed high levels of DP 1 receptor expression in ciliary epithelium/processes, ciliary muscles, the iris, and the retinal choroid, which was similar to that observed previously using the endogenous ligand [ 3 H]PGD 2 (Matsuo and Cynader, 1993). Selective radiolabeled DP 2 receptor antagonists have been reported: [ 3 H]TRQ11238 (Ulven et al, 2007), [ 3 H 3 ]QAW039 (Luu et al, 2015), and [ 3 H]OC-459 (Sykes et al, 2016) ( Fig. 1; Table 1).…”
Section: B Applications Of Radioligandssupporting
confidence: 86%
“…This study revealed high levels of DP 1 receptor expression in ciliary epithelium/processes, ciliary muscles, the iris, and the retinal choroid, which was similar to that observed previously using the endogenous ligand [ 3 H]PGD 2 (Matsuo and Cynader, 1993). Selective radiolabeled DP 2 receptor antagonists have been reported: [ 3 H]TRQ11238 (Ulven et al, 2007), [ 3 H 3 ]QAW039 (Luu et al, 2015), and [ 3 H]OC-459 (Sykes et al, 2016) ( Fig. 1; Table 1).…”
Section: B Applications Of Radioligandssupporting
confidence: 86%
“…The preparation of [ 3 H]-QAW039 has been previously described (see Luu et al, 2015 All radioligand experiments were conducted in 96 deep-well plates in assay binding buffer (Hanks' balanced salt solution containing 10 mM HEPES, 1% dimethylsufoxide (DMSO), and 0.02% pluronic acid, pH 7.4) at 37°C. In all cases, nonspecific binding was determined in the presence of 3 mM AZD-1981, a selective CRTh2 antagonist.…”
Section: Compoundsmentioning
confidence: 99%
“…For flash chromatography, in process TLC control, radio‐detection of [ 3 H]CDZ173, determination of the specific activity by MS, open access LC/MS, and service‐MS of intermediates and final products, the same hard ware equipment was used as described in detail in the experimental part of a publication from the isotope lab unit . For GC‐MS analytics of the bis‐halogenated pyridines 16 – 18 , a Waters GTC GC/MS accurate mass instrument was used.…”
Section: Methodsmentioning
confidence: 99%